Vehicle Speed at Level Crossings with Asphalt and Precast Concrete Pavement - Tri Ratna Darma Putra; Endang Widjajanti (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
Level crossings require pavement surfaces that provide a smooth and stable transition between the roadway and railway tracks. In practice, asphalt and precast concrete panels, commonly referred to as Concrete Level Crossing (CLC), are used as pavement systems at level crossings in Indonesia. Differences in pavement characteristics may influence the speed behavior of vehicles approaching and traversing the crossing. This study evaluates vehicle speed and deceleration characteristics at level crossings with asphalt and CLC pavement on two-lane, two-way rural roads in West Java, Indonesia. Field observations were conducted at JPL 40 on Jalan Raya Cibadak–Sukabumi, which uses CLC pavement, and JPL 118 on Jalan Mohamad Toha, Parung Panjang, which uses asphalt pavement. Vehicle speeds were recorded at three observation points located 100 m and 50 m before the crossing and at the crossing itself. Four vehicle categories were analyzed: motorcycles, passenger cars, medium trucks, and heavy trucks. The results show that vehicles at the CLC crossing generally recorded higher speeds at the crossing point than vehicles at the asphalt crossing. At point C, the average speeds for motorcycles, passenger cars, medium trucks, and heavy trucks were 26.27, 24.07, 28.48, and 23.90 km/h, respectively, at the CLC crossing, compared with 19.59, 20.76, 21.66, and 20.42 km/h at the asphalt crossing. Deceleration characteristics varied according to vehicle type and observation zone. These findings indicate that pavement type is associated with differences in vehicle speed behavior at level crossings and should be considered in the evaluation of crossing pavement performance.